Light and Form: Brazilian and German Photography in the 1950s. (2nd April 2016) - Valentin, Andreas
Summary: After the Second World War, Brazil underwent a rapid modernization and positioned itself in an international context, resulting also in the consolidation of the country's artistic and cultural production. Hand in hand with the repositioning of Brazilian art as seen, for instance, in the avant-garde Concrete and Neoconcrete movements, photography also renovated itself, pre-eminently in the works of José Oiticica Filho (1906–1964) and Geraldo de Barros (1923–1998). In that same period, a specific trend of European photography, particularly in Germany, also shifted towards abstraction and concretion. Noteworthy is the oeuvre of Otto Steinert and that of the fotoform and subjketive fotografie groups, which were to him connected. In those international scenarios, light and form play a fundamental role in the construction of non-objective photographs. Analysed here are the relationships between these geographically distant though formally related artistic productions.